Ramadan under the MCO is full of wisdom - UMP, PNC (2020)
Ramadan is a very beautiful and special month in the hearts of Muslims. This is a month of education and a month of faith-building, a month of self-empowerment with the best training modules to give birth to a generation of high self-esteem to meet the challenges of life.